2018
DOI: 10.1126/science.aat8642
|View full text |Cite
|
Sign up to set email alerts
|

Molecular to organismal chirality is induced by the conserved myosin 1D

Abstract: Emergence of asymmetry from an initially symmetrical state is a universal transition in Nature. Living organisms show striking asymmetries at the molecular, cellular, tissular and organismal level. However, whether and how multilevel asymmetries are related remains unclear. Here, we show that Drosophila Myosin 1D (Myo1D) and Myosin 1C (Myo1C) are sufficient to generate de novo directional twisting of cells, single organs or the whole body in opposite directions. We show that directionality lies in the Myosins’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
120
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(134 citation statements)
references
References 30 publications
1
120
1
Order By: Relevance
“…Thus, the target gene(s) of Da encodes a protein that presumably has some relationship with MyoID biochemically. Although this part of the pathway remains unknown at this point, one possibility is that the Emc‐Da cascade influences the activity of MyoID to promote F ‐actin gliding in a counterclockwise path, as observed in vitro (Lebreton et al, ).…”
Section: Discussionmentioning
confidence: 95%
“…Thus, the target gene(s) of Da encodes a protein that presumably has some relationship with MyoID biochemically. Although this part of the pathway remains unknown at this point, one possibility is that the Emc‐Da cascade influences the activity of MyoID to promote F ‐actin gliding in a counterclockwise path, as observed in vitro (Lebreton et al, ).…”
Section: Discussionmentioning
confidence: 95%
“…This effect was robust to the use of either left or right‐handed control groups, and thus was a specific property of RHLD subjects in this data set, rather than left‐handedness in general. We speculate that functional language laterality may be grounded in an evolutionarily ancient mechanism of inducing organ‐intrinsic left‐right morphogenesis, which can be traced back to the ancestral bilateria, and which arises from fundamental aspects of cellular biology and mechanics . Developmental studies will be needed to assess whether cellular chirality is transiently present before asymmetric embryonic development of the mammalian brain.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the typical form of human brain functional laterality may instead originate from a genetic‐developmental mechanism that is brain‐intrinsic. Recent studies in Drosophila have showed that cellular chirality induces left‐right asymmetry of individual organs in an organ‐intrinsic manner, without being induced by the ciliary‐nodal pathway . In these mechanisms, chirality is a transient property of whole cell morphology at key points in embryonic development .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Richard Goldschmidt called them “hopeful monsters” (Piternick, ) to stress their potential as progenitors of new species, assuming they confer an adaptive benefit (Diogo, Guinard, & Diaz, ). Saltations of this sort may have founded a few taxa (Lebreton et al, ), but they surely did not play the kind of cardinal role that Bateson and Goldschmidt envisioned (Dietrich, ; Theissen, ).…”
Section: Introductionmentioning
confidence: 99%